Potensi Daur Ulang Sampah Domestik Di Wilayah Pengembangan V Kota Pekanbaru - Rosdinar Hasibuan; Elvi Yenie; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Waste Generation , Composition and Characteristics is very important planning waste recycling systems in waste management. This research was conducted in Development Area V with a total sample of 92 respon, 69 Payung Sekaki districts and 94 Marpoyan Damai districts. Determination of domestic waste generated based on the SNI 19-3964-1994 method carried out for eight consecutive days. The results showed that the average solid for household waste in Tampan Subdistrict was 0,150 kg / person / day. While the average amount of household waste in Payung Sekaki is 0,179 kg / person / day, and the average amount of waste generation in Marpoyan Damai sub-district is 0,132 kg / person / day. The largest composition of organic waste is dominated by organic waste at 52,41%. The results of physical characteristics in the form of compaction factors were 1,14 kg/liters, and chemical characteristics for water content were 20,68%, volatile content was 62,53%, ash content was 9.69% and fixed carbon was 12,8%. The potential for household organic waste recycling in the Development Area V is divided become III step, obtained from is recycling by recycable, composting and RDF (Reduse Derived Fuel). Keywords: generation , Composition, Characteristics of waste, Recycling potential Domestic waste.